Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd001318.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for cervical intraepithelial neoplasia

Abstract: Background Cervical intraepithelial neoplasia (CIN) is the most common pre-malignant lesion. Atypical squamous changes occur in the transformation zone of the cervix with mild, moderate or severe changes described by their depth (CIN 1, 2 or 3). Cervical intraepithelial neoplasia is treated by local ablation or lower morbidity excision techniques. Choice of treatment depends on the grade and extent of the disease. Objectives To assess the effectiveness and safety of alternative surgical treatments for CIN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 60 publications
5
97
1
5
Order By: Relevance
“…5 In most countries, the excisional procedure, ie, conization, is the preferred treatment. 5 In most countries, the excisional procedure, ie, conization, is the preferred treatment.…”
mentioning
confidence: 99%
“…5 In most countries, the excisional procedure, ie, conization, is the preferred treatment. 5 In most countries, the excisional procedure, ie, conization, is the preferred treatment.…”
mentioning
confidence: 99%
“…For CIN3, there is an international consensus regarding the need for treatment [19, 20]. By contrast, clinical management is inconsistent for CIN2 findings [21-24].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cryotherapy costs substantially less, does not require electricity (it only needs transportable tanks of compressed refrigerant gases) and does not require local anesthetic [26]. Metaanalysis of randomized clinical trials evaluating the effectiveness of cryotherapy with LEEP, conization and laser concluded that all above treatment were equally effective [27] Therefore, and provided the lesion is located in the ectocervix, cryotherapy is the treatment of choice. LEEP is used in the treatment of lesions that involve the endocervical canal.…”
Section: Global Strategies Against Cancermentioning
confidence: 99%